2019
DOI: 10.1017/dsi.2019.319
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Uncertainty Framework for Product Service Systems of Systems

Abstract: Product Service Systems (PSS) are increasingly complex and collaborative. For instance, manufacturing companies, service providers, and other companies collaborate and jointly develop and operate a PSS (ex: smart grid), where its constituent elements are managed and operated independently. Managerial independence and operational independence are commonly considered key characteristics of a System of Systems (SoS). Hence, a collaborative PSS exhibits System of Systems (SoSs) characteristics. These systems have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…(2) the infrastructure, and (3) the humans and agents. 3,5 "Interfaces" define the functional and structural interfaces between heterogeneous "systems. "…”
Section: System Viewmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) the infrastructure, and (3) the humans and agents. 3,5 "Interfaces" define the functional and structural interfaces between heterogeneous "systems. "…”
Section: System Viewmentioning
confidence: 99%
“…Like PSSs, PSSoSs are heteroge-neous, and customer-oriented. 3 PSSoSs are as complex as SoSs and show diversity and emergence characteristics. 4 Thus, in the context of a PSSoS, independent stakeholders collaborate to provide a service.…”
Section: Introductionmentioning
confidence: 99%
“…A PSSoS is defined by Hein et al (2018) as a PSS showing characteristics of Systems of systems (SoSs), namely operational and managerial independence of the elements, emergent behaviour, etc (Maier, 1996). Hence, PSSoSs development raises new design challenges (Fakhfakh et al, 2019). Systems are heterogeneous and independent.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to address these new challenges by integrating the characteristics of a PSSoS into an appropriate PSSoS design method. However, PSS and SoS have been studied separately in the literature (Fakhfakh et al, 2019). Studying both PSS design methods and SoS design methods, Hein et al (2018) showed that:  PSS design methods rarely consider the increasing complexity of PSSs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation